Sintilimab for treating progressive multifocal leukoencephalopathy caused by human polyomavirus 2 virus infection following allogeneic hematopoietic cell transplantation: a case report - Xuelian Jin; Xushu Zhong; Qinyu Liu; Xinchuan Chen (Hematology)
Background: Progressive multifocal leukoencephalopathy (PML) is characterized by demyelination in the central nervous system. It is caused by infection with human polyomavirus 2 and has a poor prognosis. Therapeutic strategies involve restoring immune function and/or discontinuing immunosuppressive treatment. Immune checkpoint inhibitors such as those targeting programmed death receptor-1 (PD-1) can alleviate PML by restoring T cell function. There are no case reports on the use of the PD-1 inhibitor, Sintilimab, for treating PML. Here, we report a case of successful treatment of PML with sintilimab following allogeneic hematopoietic stem cell transplantation.Case presentation: A 35-year-old woman with high-risk acute myeloid leukemia underwent allogeneic hematopoietic stem cell transplantation after induced remission and developed PML 12 months after transplantation. She received five courses of 100 mg every 4 weeks with monitoring by magnetic resonance imaging (MRI) and viral load in the cerebrospinal fluid, showing clinical improvement, resolution of neurological symptoms, and reduced viral load. MRI showed initial exacerbation of lesions but significant improvement after five courses of treatment. No graft-versus-host disease occurred, but manageable immune reconstitution inflammatory syndrome was observed.Conclusion: Sintilimab, a PD-1 inhibitor, might be used to treat PML in patients with hematologic malignancies undergoing allo-HSCT, which needs further investigation.